A 32 μm2 MOS-Based Remote Sensing Temperature Sensor with 1.29 °C Inaccuracy for Thermal Management - Ruohan Yang; Kwabena Oppong Banahene; Bryce Gadogbe; Randall Geiger; Degang Chen (Computers)
This paper introduces a compact NMOS-based temperature sensor designed for precise thermal management in high-performance integrated circuits. Fabricated using the TSMC 180 nm process with a 1.8 V supply, this sensor employs a single diode-connected NMOS transistor, achieving a significant size reduction and improved voltage headroom. The sensor’s area is 32 µm2 per unit, enabling dense integration around thermal hotspots. A novel voltage calibration method ensures accurate temperature extraction. The measurement results demonstrate three-sigma errors within ±0.1 °C in the critical range of 75 °C to 95 °C and +1.29/−1.08 °C outside this range, confirming the sensor’s high accuracy and suitability for advanced thermal management applications.